The Effect of Promotion, Service Quality, and Price on Customer Satisfaction of Bang-Jek Blora Service Users - Pramono, Novel; Haerudin, Haerudin; Jumai, Jumai; Nurhayati, Nurhayati (Economics and Business International Conference Proceeding, 2024)
Bang-Jek focuses on food delivery with various service categories. The purpose of this study is to find out how promotion, service quality, and price have an impact on Bang-Jek Blora’s customer satisfaction. The research uses a quantitative approach. The focus of the study was 4161 Bang-Jek Blora customer contacts. A simple random sampling method was used to collect 100 respondents. The analysis method is multiple linear regression analysis. The results of the study show that Promotion does not have a significant effect on Customer Satisfaction of Bang-Jek Blora Service Users, but Service Quality and Price partially have a positive and significant effect on Customer Satisfaction Bang-Jek Blora Service Users.